Variable tap-length linear equaliser with variable tap-length adaptation step-size - Liu, Zhiyong (Electronics letters, 2014)
A simple method for dynamically adjusting the tap-length adaptation step-size of a variable tap-length linear equaliser based on the fractional tap-length algorithm is presented. Simulations show that the technique provides a fast convergence of tap-length and small steady-state tap-length fluctuation.